Are custom-made foot orthoses of any interest on the treatment of foot pain for prolonged standing workers?. (October 2019) - Tarrade, Tristan; Doucet, Fabrice; Saint-Lô, Nicolas; Llari, Maxime; Behr, Michel
Abstract: Background: The prolonged standing position is an important factor in the onset of foot musculoskeletal disorders among workers. Safety shoes, designed to protect against the physical constraints of the work environment, do not address this issue to date. Objectives: The goal of this study is to assess the possible benefits of custom-made foot orthoses among prolonged standing workers. Study design: repeated measures without control group. Methods: Thirty-four standing workers who suffer from foot pain volunteered for the study. Custom-made foot orthoses, designed by a podiatrist, were 3D-printed and distributed to each volunteer. Static balance as well as static and dynamic plantar pressure measurements were carried out with sensors inserted in the safety shoes, before and after three weeks of wearing foot orthoses daily. A questionnaire on pain and comfort was also distributed before and after treatment. Results: Feelings of pain, discomfort and heavy legs were found to be significantly reduced after wearing 3D-printed orthoses (p<0.05). Additionally, in static and dynamic conditions, a significant decrease in mean peak pressure in the rearfoot area was observed along with a significant increase in mean peak pressure in the midfoot area (p<0.05). There was also a significant improvement of balance in the medial-lateral direction. Conclusion: Custom-made orthoses significantly increase the well-being of standing workers in our experimental testing conditions. The custom-made shape allows for a better balanced distribution of foot peak pressure thanks to its support and stimulation of the foot arches particularly through a shift of pressure from the heel to the midfoot. Highlights: Feelings of pain, discomfort and heavy legs are improved with foot orthosis. Peak plantar pressure are reduced and distributed from heel toward the midfoot area. Postural stability is significantly improved in the medial-lateral direction.